Back to Basics: Necessity, Proportionality, and the Right of Self-Defence Against Non-State Terrorist Actors - Trapp, Kimberley N (The International and comparative law quarterly, 2007)
The International Court of Justice's decision in DRC v Uganda touches on, but fails to address, the circumstances under which a State has a right to use force in self-defence against non-State actors.1 In particular, the Court holds that, because the attacks carried out by anti-Ugandan rebels operating from the Democratic Republic of Congo's (DRC) territory are not attributable to the DRC, Uganda has no right to use force in self-defence against the DRC.2 The separate opinions in DRC v Uganda lament the Court's failure to take the opportunity to address the right to act in self-defence against non-State actors3–an issue of such obvious importance to the international community in an age of terrorism. As will be examined below, there are arguably good reasons–on the facts of the case–for the Court's refusal to pronounce itself on the matter. Furthermore, its decision need not be read as absolutely precluding a use of force in foreign territory in response to armed attacks by non-State actors.